Pengaruh Pelatihan Kerja Kompensasi Finansial dan Pengembangan Karir terhadap Kinerja Karyawan - Suwidia, I Putu; Ardani, Wayan; Widani, Made (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2023)
The aim of this research is to determine the effect of job training, financial compensation and career development on employee performance at the CV Best Indonesian Gift Company. The method for determining the sample in this research is using saturated sampling (census). The total sample was 36 respondents. The data analysis techniques used in this research are Validity Test, Reliability Test, Classical Assumptions, and Multiple Linear Regression Analysis. The results of this study indicate that job training (X1), financial compensation (X2), and career development (X3), is assumed to be equal to 0 (zero), then employee performance (Y) will increase. The results of this study indicate that job training (X1), financial compensation (X2), and career development (X3) is assumed to be equal to 0 (zero), then employee performance (Y) will increase. Test the significance of multiple correlation using the F test, simultaneously job training, financial compensation and career development have a positive and significant effect on employee performance. The significance test uses the t test, partially job training, financial compensation and career development have a positive and significant effect on employee performance at the CV Best Indonesian Gift Company.